3-Dimensional flower-like clusters of CoNiP nanofoils in-situ grown on randomly-dispersed rGO-Nanosheets with superior electrocatalysis for hydrogen evolution reactions. (21st May 2019) - Huang, Ming; Ge, Kang; Dong, Guodian; Zhou, Zhihao; Zeng, Yanwei
Abstract: It has been being an interesting challenge to develop novel electrocatalysts with advantageous nanostructures and thereby-improved catalytic performance for hydrogen evolution reaction (HER) over the past years. Herein, we report on the flower-like clusters of CoNiP nanofoils thickly grown on the randomly-interconnected reduced graphene oxide (rGO) nanosheets (CoNiP-NF/rGO) of 3-dimensional framework architecture, which has been successfully achieved via an optimized solvothermal process with Ni-doped ZIF-67 (Ni-ZIF-67) dodecahedral particles as the precursor and graphene oxide (GO) nanosheets as the substrate for the in-situ growth of flower-like CoNi-hydroxides nanofoils, as well as a following topotactic transformation in a controlled phosphorization. Benefiting from its distinctly advantageous nanostructures featured with extremely high specific surface area, enriched catalytic active sites and enhanced electronic transportation, the as-prepared CoNiP-NF/rGO exhibits an excellent electrocatalytic performance of HER with an onset overpotential of 33 mV, an overpotential of 82 mV at 10 mA cm −2, a Tafel slope of 37 mV dec −1 and a high chemical stability in acidic solutions. Such an advantageous nanostructure and its positive influences on the electrocatalytic performance are useful for the preparation of other nonprecious metal electrocatalysts. Highlights: Ni doping can tune electronic structure of Co center to boost the intrinsic activity. The formation of Co-Ni hydroxide through the topotactic transformation of Ni-ZIF-67. The CoNiP nano-foils were structurally a build-up of numerous crystallites. The adjustment of nitrate can modulate the morphology of CoNiP nano-foils.